Morphometric Analysis of Fibularis Tertius Muscle in Eastern Indian Population: A Cross-Sectional Study - Gyanaranjan Nayak (Highlights on Medicine and Medical Science Vol. 12, 2021)
Introduction: Fibularis tertius is a human-only unipennate extensor compartment muscle. Foot surgeons employ the Fibularis tertius muscle flap to transpose the ankle joint and fix any laxity. As seen in certain foot fractures, variable muscle insertion may play a role in the cause of torsional stress. Aim: To investigate the incidence of the fibularis tertius muscle, as well as its dimensions and variations in origin and insertion in cadaveric limbs. Materials and Methods: The incidence, size, and variations in the origin and insertion of the fibularis tertius muscle were determined by dissecting 100 cadaveric lower limbs (50 right and 50 left). Results: All of the limbs included Fibularis tertius.It was placed between the fourth and fifth metatarsals. The muscle’s length and width, as well as its tendon, were measured. Conclusion: Because the distal attachment of the fibularis tertius is varied, foot surgeons must have a thorough understanding of the muscle when doing tendoplasty or tendon transfer surgeries.